ISO 14001 certification and financial performance of companies / Ong Tze San …[et al.] - Ong, Tze San; Teh, Boon Heng; Goh, Han Hwa; Thai, Siew Bee (Penerbit UiTM (UiTM Press), 2015)
This study aims to investigate the relationship between ISO 14001 certification and financial performance and to ascertain whether the ISO 14001 accreditation has improved the financial performance of a sample of Malaysian publicly listed companies. ISO 14001, which is the most recognized framework for establishing environmental management, helps companies to account for the influence of their activities on the environment and to demonstrate sound environmental management. The linear regression analysis shows that firms with above-average performance have a greater tendency to pursue ISO 14001 accreditation. A significant relationship is also established between ISO 14001 certification and financial performance in the context of an emerging economy. The adoption of ISO 14001 benefits companies by enhancing their reputation and brand awareness on the one hand and increasing their sales and investor confidence on the other.